2010
DOI: 10.1038/labinvest.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Vascular corrosion casting: analyzing wall shear stress in the portal vein and vascular abnormalities in portal hypertensive and cirrhotic rodents

Abstract: Vascular corrosion casting is an established method of anatomical preparation that has recently been revived and has proven to be an excellent tool for detailed three-dimensional (3D) morphological examination of normal and pathological microcirculation. In addition, the geometry provided by vascular casts can be further used to calculate wall shear stress (WSS) in a vascular bed using computational techniques. In the first part of this study, the microvascular morphological changes associated with portal hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Filling of the blood vessels with a casting polymer and subsequent removal of all the surrounding tissue allows for an accurate and three-dimensional study of the vascular structures by scanning electron microscopy at high levels of magnification that cannot be achieved by angiography-based imaging techniques, which do not attain the same resolution at the microvascular level. 26,39 The casts of the animals with steatosis showed a marked alteration of liver microvascular architecture. The classical ordering of sinusoids in parallel lines and separated by regular trabeculae of hepatocytes was replaced by a completely disorganized pattern of irregular and flattened blood vessels with numerous interconnections and the presence of multiple 'blebs', that is, blind-ending rounded extensions of the sinusoids, which might represent obstructed sinusoids or leakage by disruption of the normal sinusoidal wall.…”
Section: Intrahepatic Resistance In Steatosis S Francque Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Filling of the blood vessels with a casting polymer and subsequent removal of all the surrounding tissue allows for an accurate and three-dimensional study of the vascular structures by scanning electron microscopy at high levels of magnification that cannot be achieved by angiography-based imaging techniques, which do not attain the same resolution at the microvascular level. 26,39 The casts of the animals with steatosis showed a marked alteration of liver microvascular architecture. The classical ordering of sinusoids in parallel lines and separated by regular trabeculae of hepatocytes was replaced by a completely disorganized pattern of irregular and flattened blood vessels with numerous interconnections and the presence of multiple 'blebs', that is, blind-ending rounded extensions of the sinusoids, which might represent obstructed sinusoids or leakage by disruption of the normal sinusoidal wall.…”
Section: Intrahepatic Resistance In Steatosis S Francque Et Almentioning
confidence: 99%
“…15 Vascular Corrosion Casts Vascular corrosion casting was performed as previously described. 26 After overnight fasting animals fed the MCD diet (n ¼ 5) or the control diet (n ¼ 5) were killed by means of an intraperitoneal injection of an overdose of a solution containing 0.8 ml ketamin (Anesketin, Eurovet, Heusden-Zolder, Belgium) and 0. Methoxamine and ACh were purchased from Sigma-Aldrich Chemie Gmbh, Steinheim, Germany.…”
Section: In Situ Liver Perfusion Studiesmentioning
confidence: 99%
“…IA has been observed in different murine disease models, including models of liver cirrhosis, models of inflammation, and the hypoxic mouse retina [56,57,58]. In addition, IA was observed to start glomerular repair after induced Thy-1.1 nephritis in rats [59,60].…”
Section: Intussusceptive Angiogenesismentioning
confidence: 99%
“…Geometries were Closed-loop lumped parameter modelling of hemodynamics during cirrhogenesis in rats based on CT-scans and results indicated that -in the case of cirrhosis -right-lobe atrophy was significantly influenced by the distribution of splenic venous blood. Van Steenkiste et al [11] used vascular corrosion casting (VCC) to study vascular morphological changes and CFD simulations to compute PV wall shear stresses in portal hypertensive and cirrhotic rodents. Additional to the macrocirculatory research, only few studies have focused on modelling the hepatic microcirculation of healthy and cirrhotic livers.…”
Section: Introductionmentioning
confidence: 99%